Awareness of and Barriers to Low Vision Services Among Eye Care Practitioners in Goa. - Usgaonkar, Ugam P. S.; Sawaiker, Aakanksha D.; Shetty, Aksha (Optometry & Visual Performance, 2023)
Background: The purpose of this study was to identify the knowledge of and perceived barriers to providing low vision services among eye care practitioners in Goa. Methods: A pretested and predesigned questionnaire was sent to 72 eye care practitioners, which included the optometrists and ophthalmologists working in Goa, through offline and online (social media like WhatsApp, Instagram, etc.) platforms. Information was collected to understand the barriers that restrict eye care practitioners from providing low vision services. Results: Seventy-two participants took part in this study, of which 26.39% (n=19) were ophthalmologists and 73.61% (n=53) were optometrists. From the practitioner's point of view, lack of awareness (70.83%, n=51) and training (68.06%, n=49) were the major barriers to providing low vision services. Conclusion: A lack of awareness and training facilities among eye care practitioners acts as a barrier to providing low vision services.